The skull of Homo naledi. Issue 104 (March 2017) - Laird, Myra F.; Schroeder, Lauren; Garvin, Heather M.; Scott, Jill E.; Dembo, Mana; Radovčić, Davorka; Musiba, Charles M.; Ackermann, Rebecca R.; Schmid, Peter; Hawks, John; Berger, Lee R.; de Ruiter, Darryl J.
Abstract: The species Homo naledi was recently named from specimens recovered from the Dinaledi Chamber of the Rising Star cave system in South Africa. This large skeletal sample lacks associated faunal material and currently does not have a known chronological context. In this paper, we present comprehensive descriptions and metric comparisons of the recovered cranial and mandibular material. We describe 41 elements attributed to Dinaledi Hominin (DH1–DH5) individuals and paratype U.W. 101-377, and 32 additional cranial fragments. The H. naledi material was compared to Plio-Pleistocene fossil hominins using qualitative and quantitative analyses including over 100 linear measurements and ratios. We find that the Dinaledi cranial sample represents an anatomically homogeneous population that expands the range of morphological variation attributable to the genus Homo . Despite a relatively small cranial capacity that is within the range of australopiths and a few specimens of early Homo, H . naledi shares cranial characters with species across the genus Homo, including Homo habilis, Homo rudolfensis, Homo erectus, and Middle Pleistocene Homo . These include aspects of cranial form, facial morphology, and mandibular anatomy. However, the skull of H. naledi is readily distinguishable from existing species of Homo in both qualitative and quantitative assessments. Since H . naledi is currently undated, we discuss the evolutionary implications of its cranial morphology in a range of chronological frameworks. Finally, we designate a sixth Dinaledi Hominin (DH6) individual based on a juvenile mandible.